2019
DOI: 10.3389/fonc.2019.01114
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Identification of miR-622 Key Target Genes and Experimental Validation of the miR-622-RNF8 Axis in Breast Cancer

Abstract: Breast cancer is the leading cause of cancer-associated deaths among females. In recent decades, microRNAs (miRNAs), a type of short non-coding RNA that regulates gene expression at the post-transcription level, have been reported to participate in the regulation of many hub genes associated with tumorigenesis, tumor progression, and metastasis. However, the precise mechanism by which miRNAs regulate breast cancer metastasis remains poorly discussed, which limits the opportunity for the development of novel, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 55 publications
5
20
0
Order By: Relevance
“…Recently, Liu reported, from in silico analysis, that in all breast cancer patients of the TCGA dataset, survival rate was negatively correlated with high level of miR-622. 21 However, we found that by analysing specific subtypes of breast cancers, high levels of miR-622 positively correlated with overall survival in the TNBC, ER-neg, HER2-pos and luminal B subtypes. These different results could be explained by the fact that breast cancer is an extremely heterogenous disease.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Recently, Liu reported, from in silico analysis, that in all breast cancer patients of the TCGA dataset, survival rate was negatively correlated with high level of miR-622. 21 However, we found that by analysing specific subtypes of breast cancers, high levels of miR-622 positively correlated with overall survival in the TNBC, ER-neg, HER2-pos and luminal B subtypes. These different results could be explained by the fact that breast cancer is an extremely heterogenous disease.…”
Section: Discussionmentioning
confidence: 74%
“… 20 In glioma miR-622 targets YAP 11 and in breast cancer targets RNF8. 21 Finally, a recent paper reported that in renal cell carcinoma, miR-622 suppressed cancer progression by targeting CCL18. 22 …”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are a class of endogenous noncoding small RNAs that play an important role in post-transcriptional gene silencing via partially or completely complementary binding to target mRNAs in their 3’ UTRs 23,36 . Currently, multiple researchers have confirmed that miRNAs are involved in the mechanisms of most biological processes including excessive growth, resistance to apoptosis, angiogenesis, invasion, and metastasis 35,37 .…”
Section: Discussionmentioning
confidence: 99%
“…The intersection of the results obtained from these tools allowed identifying 77 promising targets and constructing a protein-protein interaction network. The results were experimentally validated in vitro, revealing the regulatory mechanisms of miR-622 in breast cancer cells [ 61 ].…”
Section: Mirna Target Predictionmentioning
confidence: 99%